2012
DOI: 10.1111/j.1600-051x.2012.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic effects of orally administered Lactobacillus reuteri‐containing tablets on the subgingival and salivary microbiota in patients with gingivitis. A randomized clinical trial

Abstract: The effect of L. reuteri administered in tablets resulted in a reduction in the number of selected periodontal pathogens in the subgingival microbiota, without an associated clinical impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
197
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(213 citation statements)
references
References 23 publications
9
197
1
6
Order By: Relevance
“…Furthermore, the suppression of inflammatory cytokine production in gingival tissue by gastric administration of LG2055 may correlate with β-defensin production in oral sites. Since the administration of tablets containing Lactobacillus reuteri significantly decreased the number of periodontal pathogens in the subgingival microbiota and was effective as an adjunct to scaling and root planing in chronic periodontitis in a randomized clinical trial 35, 36 , it is probable that the results observed in our animal experiment will also be seen in the human oral cavity in clinical trials. Further study is required regarding the detailed mechanism underlying the induction of β-defensin production in the oral cavity by gastric administration of LG2055.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the suppression of inflammatory cytokine production in gingival tissue by gastric administration of LG2055 may correlate with β-defensin production in oral sites. Since the administration of tablets containing Lactobacillus reuteri significantly decreased the number of periodontal pathogens in the subgingival microbiota and was effective as an adjunct to scaling and root planing in chronic periodontitis in a randomized clinical trial 35, 36 , it is probable that the results observed in our animal experiment will also be seen in the human oral cavity in clinical trials. Further study is required regarding the detailed mechanism underlying the induction of β-defensin production in the oral cavity by gastric administration of LG2055.…”
Section: Discussionmentioning
confidence: 94%
“…Several in vitro studies (Teughels et al, 2007; van Essche et al, 2012) and recent clinical studies (Iniesta et al, 2012; Teughels et al, 2013; Yanine et al, 2013) have suggested that these allegedly beneficial bacteria can cause antagonism toward Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from its previously described positive contributions in the heath of oral (Iniesta et al, 2012; Martin-Cabezas et al, 2016) and gastrointestinal (GI) tract mucosa (Cruchet et al, 2015; Gao et al, 2015; Liu et al, 2012; Schreiber et al, 2009; Varian et al, 2016a; Walter et al, 2011), the probiotic has systemic effects on the immune and hormonal profile of the host animal (Buffington et al, 2016; Erdman and Poutahidis, 2014; Ibrahim et al, 2014; Lakritz et al, 2014; Lee et al, 2016; Levkovich et al, 2013; Livingston et al, 2010; Poutahidis et al, 2013a,b, 2014, 2015; Simon et al, 2015; Varian et al, 2016a,b, 2014). Mice that consume L. reuteri live longer (Ibrahim et al, 2014; Varian et al, 2016a) and resist obesity (Fak and Backhed, 2012; Poutahidis et al, 2013b; Qiao et al, 2015; Varian et al, 2016b, 2014) and age-associated atrophic changes of skeletal muscle (Varian et al, 2016a), testis (Poutahidis et al, 2014), and thyroid (Varian et al, 2014) and thymus glands (Varian et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%